Preparation and Antifungal Activity Investigation of Oligochitosan-Zn2+ on Colletotrichum truncatum - Dang Van Phu; Bui Duy Du; Le Nghiem Anh Tuan; Le Thanh Hung; Hoang Dac Hiet; Nguyen Quoc Hien (International Journal of Polymer Science)
This study presents the structural characteristics and the antifungal efficiency of the oligochitosan-Zn2+ complexes. Oligochitosan with the average molecular weight of ~5 kDa was effectively prepared by gamma-ray irradiation degradation of chitosan in a solution containing H2O2. The oligochitosan-Zn2+ complexes with the different molar ratios of -NH2/Zn2+ were prepared by mixing Zn(NO3)2 into oligochitosan solution. The resultant complexes were characterized by FTIR, XRD, UV-Vis, and ICP-AES. The obtained results demonstrated that Zn2+ ions were stably bound with oligochitosan molecules through interacting with -OH and -NH2 groups. The in vitro antifungal effect of oligochitosan-Zn2+ complexes was assessed against Colletotrichum truncatum, a fungus species causing anthracnose on crops. The antifungal activity was significantly improved as the increase of Zn2+ content in the complexes. Particularly, the antifungal efficiency of the complexes reached to 75–100% compared to that of about 12% for oligochitosan. Thus, the addition of Zn2+ into oligochitosan strengthens its performance towards antifungal property and bring forward a new approach for progressing biobased materials for controlling plant diseases.